Psychometrics as a Tool to Improve Screening and Access to Credit - Irani Arráiz; Miriam Bruhn; Rodolfo Stucchi (Inter-American Development Bank (IDB), 2015)
This paper studies the use of psychometric tests, designed by the Entrepreneurial Finance Lab (EFL), as a tool to screen out high credit risk and potentially increase access to credit for small business owners in Peru. We use administrative data covering the period from June 2011 to April 2014 to compare debt accrual and repayment behavior patterns across entrepreneurs who were offered a loan based on the traditional credit-scoring method versus the EFL tool. We find that the psychometric test can lower the risk of the loan portfolio when used as a secondary screening mechanism for already banked entrepreneurs - i.e., those with a credit history. For unbanked entrepreneurs - i.e., those without a credit history - using the EFL tool can increase access to credit without increasing portfolio risk.
hdl:11319/7266
Keywords: D82; G21; G32; 330; Asymmetric information; psychometric tests; credit risk; access to credit